Highly sensitive electrochemical determination of neutrophil gelatinase-associated lipocalin for acute kidney injury - Kannan, Palanisamy (2013)
A label-free electrochemical immunosensor for the detection of neutrophil gelatinase-associated lipocalin (NGAL) is developed by the immobilization of rabbit polygonal lipocalin-2 antibody on gold nanoparticles attached on generation-1polyamidoamine (PAMAM) dendrimer (LA2/AuNPs/PAMAM)-modified gold electrode. The modification procedure was characterized by UV–vis, surface enhanced Raman spectroscopy and field-emission scanning electron microscopy techniques. The detection of NGAL is based on the enhancement of oxidation current on the modified electrodes upon the antigen–antibody interaction. The electrochemical immunosensor exhibited high sensitivity (1 ng mL−1 (280 pM) based on the signal-to-noise ratio 3), wide linear range (50–250 ng mL−1) and long-term stability. The reliability of the developed immunosensor was investigated by the detection of NGAL in both blood serum and urine samples.